Alternatif Pemerataan Pendidikan Kementerian Pendidikan: Studi Repatriasi Anak Pekerja Migran Kota Blitar - Yusuf Agung Bintoro; Wisnu; Muhammad Jacky; Haliza Aflin Syauky Rosidin (Research and Development Agency Ministry of Home Affairs, 2025)
Equal access to education is part of fulfilling the rights of citizens, both within the country and abroad. The government, through the Ministry of Education, repatriates the children of migrant workers to obtain the right to study in Indonesia through partner schools of the Ministry of Education and Culture. This study analyzes repatriation as an educational alternative for the children of Indonesian migrant workers. Lack of documentation is a problem for them regarding administrative requirements, especially in education. Data was collected through observation and interviews with repatriates. Data collection was considered easy because the researcher was directly involved in the daily activities of the repatriates. Field findings indicate that their current course of study helps with their education and living expenses. Despite language difficulties, they feel comfortable because a representative educational environment supports them. Their adaptation is also fast because there are several similarities between Blitar and their origins while abroad. The purpose of repatriation in the field of education is none other than educational equality. Collaborative support from the government (Ministry of Education) and the person responsible for repatriation in Blitar makes repatriates feel at ease pursuing education in Indonesia. The learning environment influences the latent pattern of nationalist character formation for repatriates. Many factors shape the social resilience of repatriates.